Trigonometry

Simplify the expression using trig identities:
1. (sin4x - cos4x)/(sin2x -cos2x)

2. (sinx(cotx)+cosx)/(2cotx)

  1. 👍 0
  2. 👎 0
  3. 👁 551
  1. 1.
    I am sure you mean
    (sin^4 x - cos^4 x)/(sin^2 x - cos^2 x)
    = (sin^2 x + cos^2 x )((sin^2 x - cos^2 x)/(sin^2 x - cos^2 x)
    = (sin^2 x + cos^2 x)
    =1

    2.
    (sinx(cotx)+cosx)/(2cotx)
    = (sinx(cosx/sinx) + cosx)/(2cosx/sinx)
    = (cosx + cosx)(sinx/(2cosx)
    = 2cosx(sinx)/(2cosx)
    = sinx

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. math(advanced algebra&trigonometry)

    the expression cos4x cos3x + sin4x sin3x is equivalent to which one of the following is the answer: 1) sinx 2) sin7x 3) cosx 4) cos7x

  2. Trig.......

    I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30ยบ, the two sides are not equal, they differ by 1 oh , thank you Mr

  3. math;)

    The equation 2sinx+sqrt(3)cotx=sinx is partially solved below. 2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx) 2sin^2x+sqrt(3)cosx=sin^2x sin^2x+sqrt(3)cosx=0 Which of the following steps could be included in the

  4. Math - Trig - Double Angles

    Prove: sin2x / 1 - cos2x = cotx My Attempt: LS: = 2sinxcosx / - 1 - (1 - 2sin^2x) = 2sinxcosx / - 1 + 2sin^2x = cosx / sinx - 1 = cosx / sinx - 1/1 = cosx / sinx - sinx / sinx -- Prove: 2sin(x+y)sin(x-y) = cos2y - cos2x My

  1. trig

    sinx = 4/5 and x terminates in Quadrant II Find sin2x and cos2x How to get the answers, which are sin2x = -24/25, cos2x = -7/25?

  2. Trig

    Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.

  3. Trig Identities

    Prove the following identities: 13. tan(x) + sec(x) = (cos(x)) / (1-sin(x)) *Sorry for any confusing parenthesis.* My work: I simplified the left side to a. ((sinx) / (cosx)) + (1 / cosx) , then b. (sinx + 1) / cosx = (cos(x)) /

  4. Math

    (sinx - cosx)(sinx + cosx) = 2sin^2x -1 I need some tips on trigonometric identities. Why shouldn't I just turn (sinx + cosx) into 1 and would it still have the same identity?

  1. trigonometry

    how do i simplify (secx - cosx) / sinx? i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx) and then i changed sec x to 1/ cosx so that i had ((1/cosx)/ sinx) - (cos x / sinx) after that i get stuck

  2. TRIGONOMETRY *(MATHS)

    Q.1 Prove the following identities:- (i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.

  3. Identities

    Verify the following identity cos2x/sin2x+sinx/cosx=csc2x

  4. trigonometry

    Been trying this forever so it says: Simplify 1+sin2x+cos2x/1+sin2x-cos2x ive tried this problem so many times I need help with it...

You can view more similar questions or ask a new question.